2023
DOI: 10.1038/s41598-023-49516-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost photocatalytic membrane modified with green heterojunction TiO2/ZnO nanoparticles prepared from waste

Sahar A. Mousa,
Heba Abdallah,
S. A. Khairy

Abstract: The combination of photocatalysis and membrane procedures represents a promising approach for water treatment. This study utilized green synthesis methods to produce TiO2 nanoparticles (NPs) using Pomegranate extract and ZnO nanoparticles using Tangerine extract. These nanoparticles were then incorporated into a polyvinyl chloride (PVC) nanocomposite photocatalytic membrane. Different devices were used to examine the properties of nanocomposite membranes. The prepared membranes' morphology was examined using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 101 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…This makes photocatalytic membranes promising candidates for sustainable and efficient water treatment processes. Several studies have demonstrated the effectiveness of photocatalytic membranes in various water treatment applications [11][12][13][14][15][16]. Moreover, the integration of photocatalytic materials into membrane structures can enhance the selectivity and specificity of membranes for particular contaminants, making them suitable for targeted water treatment applications.…”
Section: Introductionmentioning
confidence: 99%
“…This makes photocatalytic membranes promising candidates for sustainable and efficient water treatment processes. Several studies have demonstrated the effectiveness of photocatalytic membranes in various water treatment applications [11][12][13][14][15][16]. Moreover, the integration of photocatalytic materials into membrane structures can enhance the selectivity and specificity of membranes for particular contaminants, making them suitable for targeted water treatment applications.…”
Section: Introductionmentioning
confidence: 99%